Structural and photophysical investigation of single-source evaporation of CsFAPbI3 and FAPbI3 perovskite thin films. Issue 27 (30th June 2022) - Klipfel, Nadja; Haris, Muhammed P. U.; Kazim, Samrana; Sutanto, Albertus Adrian; Shibayama, Naoyuki; Kanda, Hiroyuki; Asiri, Abdullah M.; Momblona, Cristina; Ahmad, Shahzada; Nazeeruddin, Mohammad Khaja
Abstract : Single source vacuum deposition is a stimulating technique for upscaling perovskite solar cells. Abstract : Thermal vacuum deposition is a stimulating technique for upscaling perovskite solar cells. However, the operational complexity of multisource vapor deposition (MSVD) and achieving stoichiometric perovskite layers may impede its implementation. The single-source vapor deposition (SSVD) method has recently emerged as an alternative for MSVD due to its inherent functionality and ease of operation. Here, for the first time, we demonstrate a successful SSVD approach for fabricating pure CsFAPbI3 and FAPbI3 thin films from pre-synthesized perovskite powders. We carried out structural and photophysical investigations to optimize the phase purity and shelf-life of the deposited thin films. Furthermore, we probed the perovskite layer compatibility with various underlayers; we noted that MeO–2PACz, an organic underlayer, displayed superiority over other organic underlayers such as Spiro-OMeTAD and TaTm, and the SnO2 metal oxide layer, which might indicate that this method is more suitable for p–i–n solar cell fabrication. Our approach presents a straightforward methodology and avoids the use of multiple thermal sources to deposit CsFAPbI3 and can further ease the vacuum deposition methodology.